Regenerative endodontics - dos Reis-Prado, Alexandre Henrique; de Castro Oliveira, Sabrina; de Arantes, Lara Cancella; Goto, Juliana [UNESP]; Benetti, Francine (My University, 2022)
Pulp-dentin complex of immature permanent teeth can be damaged through microbial invasion caused by untreated tooth decay, trauma, and dental anomalies, consequently leading to pulp necrosis and incomplete root development without early intervention. Regenerative endodontic procedure (REP) has become a remarkable option of treatment for necrotic immature teeth compared to conventional root canal therapy. In addition to providing not only for a resolution of pain and periapical lesion, REP also allows an immunocompetent tissue formation into root canal space, resulting in continued root development through increased root length/thickness and apical closure. This approach relies on three principles of tissue engineering (signaling molecules release, stem cell proliferation, and a 3-dimensional scaffold), and requires a bacterial-free environment for more successful and more predictable long-term results. Histological studies with animals and humans have reported tissue repair rather than regeneration after REP. Clinical trials and long-term evaluations exploring new materials, protocols, and patient-centered outcomes are also necessary for REP in an effort to fill the gaps and provide stronger evidence in this field. This chapter will provide an overview of clinical indications and techniques in REP, in addition to discussing the new pathways of this therapy in endodontics.
Keywords: Conservative treatment; Growth factor(s); Guided tissue regeneration; Regenerative endodontics; Stem cells; Tissue engineering